If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -4x(x + -3)(x + 2)(2x + -1) Reorder the terms: y = -4x(-3 + x)(x + 2)(2x + -1) Reorder the terms: y = -4x(-3 + x)(2 + x)(2x + -1) Reorder the terms: y = -4x(-3 + x)(2 + x)(-1 + 2x) Multiply (-3 + x) * (2 + x) y = -4x(-3(2 + x) + x(2 + x))(-1 + 2x) y = -4x((2 * -3 + x * -3) + x(2 + x))(-1 + 2x) y = -4x((-6 + -3x) + x(2 + x))(-1 + 2x) y = -4x(-6 + -3x + (2 * x + x * x))(-1 + 2x) y = -4x(-6 + -3x + (2x + x2))(-1 + 2x) Combine like terms: -3x + 2x = -1x y = -4x(-6 + -1x + x2)(-1 + 2x) Multiply (-6 + -1x + x2) * (-1 + 2x) y = -4x(-6(-1 + 2x) + -1x * (-1 + 2x) + x2(-1 + 2x)) y = -4x((-1 * -6 + 2x * -6) + -1x * (-1 + 2x) + x2(-1 + 2x)) y = -4x((6 + -12x) + -1x * (-1 + 2x) + x2(-1 + 2x)) y = -4x(6 + -12x + (-1 * -1x + 2x * -1x) + x2(-1 + 2x)) y = -4x(6 + -12x + (1x + -2x2) + x2(-1 + 2x)) y = -4x(6 + -12x + 1x + -2x2 + (-1 * x2 + 2x * x2)) y = -4x(6 + -12x + 1x + -2x2 + (-1x2 + 2x3)) Combine like terms: -12x + 1x = -11x y = -4x(6 + -11x + -2x2 + -1x2 + 2x3) Combine like terms: -2x2 + -1x2 = -3x2 y = -4x(6 + -11x + -3x2 + 2x3) y = (6 * -4x + -11x * -4x + -3x2 * -4x + 2x3 * -4x) y = (-24x + 44x2 + 12x3 + -8x4) Solving y = -24x + 44x2 + 12x3 + -8x4 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -24x + 44x2 + 12x3 + -8x4
| 5s^2-7=0 | | -5d^2-7d-2=0 | | -2w^2+7w-1=0 | | A=3.14(10) | | -1000/8= | | (-10)(-10)(-10)= | | A=3.14(10)2 | | 3x+10=2x-50 | | (3c-7)(2c-5)= | | 2m+6n+4m+8n= | | 37-29=4 | | 2x-4=2(5+x) | | -80+360= | | =12+6(8m-3) | | (90)(-4)= | | 4yx^4*2x^2y^5=0 | | 13/9x2/3 | | 4xy*3xy^5*4x^4y^2=0 | | 4m^2*n=0 | | x-.3x=8000 | | x/43=-75-87 | | 3x-5*2=15 | | x^3y^5*x^5y^4=0 | | 10k^2-13k-9=0 | | 25+5x=x | | 8x^3-25x^2+18x=0 | | 15d-5(4d-7)=10 | | 12x^3-60x^2+63x=0 | | 4x^4-33x^3-27x^2=0 | | 25+(x+5)=x+6 | | 30v^2+145v+150=0 | | 50v^3-135v^2-140v=0 |